Computational Technologies in Geopolymer Concrete by Partial Replacement of C&D Waste - Mohan, A.; K, Sudhan (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Since geopolymers can effectively recycle waste and greatly cut greenhouse gas emissions, they a been acknowledged as a potential alternative to ordinary Portland cement (OPC), offering a greener option. Because to its accessibility and high amounts of silica and alumina, Construction and demolition waste (CDW) has lately been recognized as a source of supplies for geopolymers. This study set out to evaluate the present state of the art regarding the creation of Concrete, cement, and paste made of geopolymers as well as their characteristics, with a focus on geopolymers that incorporate C&D Wastes. The analysis includes a brief evaluation of employing C&D waste, geopolymer design mixture mixes, as well as an analysis of the key variables affecting the effectiveness of geopolymer including CDW. The financial and environmental effects of employing recycled resources in the production of geopolymer concretes are also reviewed, along with most recently information pertaining to mechanical and robustness qualities of Geopolymers based on C&D waste. Although there are many potential uses for geopolymer concretes, there are still a number of obstacles in the way of their commercialization in the construction sector. According to the review, it is feasible to create geopolymer concretes with qualities similar to those of OPC-based ones using CDW-based materials; nevertheless, choosing the right materials should be properly analyzed. addressed, particularly under typical curing circumstances.